2023
DOI: 10.1039/d3nj01374j
|View full text |Cite
|
Sign up to set email alerts
|

Macroscale preparation of nanosized calcium carbonate by exploiting biogas slurry synchronous metathesis encapsulation method

Abstract: The excessive biogas slurry produced by anaerobic fermentation seriously constrains the sustainable development of biogas industry. It was significantly important to realize resource utilization of biogas slurry. However, biogas slurry...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This result illustrates that the CNCC was completely decomposed at this high temperature. Its weight loss was about 5% at 700 • C. This might be because the HA coating material was volatilized above 650 • C. The TCA curve of CNCC was a little different from the previous result of the HA-NCC sample in reference [32], and CaCO 3 was not completely decomposed below 800 • C [2,38]. Figure 4b shows the N 2 adsorption-desorption isotherm of CNCC.…”
Section: Tga and Betmentioning
confidence: 78%
See 4 more Smart Citations
“…This result illustrates that the CNCC was completely decomposed at this high temperature. Its weight loss was about 5% at 700 • C. This might be because the HA coating material was volatilized above 650 • C. The TCA curve of CNCC was a little different from the previous result of the HA-NCC sample in reference [32], and CaCO 3 was not completely decomposed below 800 • C [2,38]. Figure 4b shows the N 2 adsorption-desorption isotherm of CNCC.…”
Section: Tga and Betmentioning
confidence: 78%
“…The COD concentration declined from 4018 mg/L to 2649 mg/L. This result indicated that 34% of HA participated in the reaction to produce CaCO 3 from biogas slurry [ 32 ]. The solution of CaCl 2 was put into the biogas slurry to cause a double decomposition reaction, forming a crystal nucleus of calcium carbonate (CaCO 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations